2022
DOI: 10.3390/cancers14020294
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of CXCL13/CXCR5 Signaling in Immune Checkpoint Inhibitor Treatment in Cancer

Abstract: Immune checkpoint inhibitors (ICIs), including antibodies that target programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), or cytotoxic T lymphocyte antigen 4 (CTLA4), represent some of the most important breakthroughs in new drug development for oncology therapy from the past decade. CXC chemokine ligand 13 (CXCL13) exclusively binds CXC chemokine receptor type 5 (CXCR5), which plays a critical role in immune cell recruitment and activation and the regulation of the adaptive immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 148 publications
(167 reference statements)
4
34
0
Order By: Relevance
“…CXCL13 acts as a B-cell chemoattractant in lymphoid neogenesis and is widely involved in the autoimmune pathogenesis and lymphoproliferative disorders. Currently, CXCL13 has been found overexpressed in malignant tissues and coordinates tumor progression by modulating cell-cell interactions and lymphocyte recruitment in the TME ( 33 , 42 , 50 ). TAMs are the most abundant non-neoplastic cell population in refractory glioma that lead to tolerogenic TME and therapeutic resistance ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL13 acts as a B-cell chemoattractant in lymphoid neogenesis and is widely involved in the autoimmune pathogenesis and lymphoproliferative disorders. Currently, CXCL13 has been found overexpressed in malignant tissues and coordinates tumor progression by modulating cell-cell interactions and lymphocyte recruitment in the TME ( 33 , 42 , 50 ). TAMs are the most abundant non-neoplastic cell population in refractory glioma that lead to tolerogenic TME and therapeutic resistance ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with recent studies, CXCL13/CD163 double staining results confirmed that CXCL13 is secreted by a variety of cells within the TME, including tumor cells and tumor-infiltrating immune cells. It specifically binds to the corresponding receptor CXCR5, directly regulating tumor progression or indirectly modulating adaptive immune responses ( 50 , 60 , 61 ). Notably, CXCL13 drives M2c activation through IL-10 induction and results in poor immunogenicity and immunosuppression ( 48 , 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…From current indications, CXCL13 and its receptor CXCR5 could be involved in the pathophysiology of HP being an autoimmune-related disorder and therefore deserve full investigation for the possible unveiling of novel effectors and therapeutic opportunities. The strong evidence for the crucial involvement of the CXCR5 : CXCL13 axis in lymphoid cell biology and in facilitating cell-cell interactions that promote lymphocyte infiltration [ 26 ] fuels speculation of potentially successful immune-targeted therapies in patients with hypersensitivity pneumonitis.…”
Section: The Role and Therapeutic Relevance Of CXC Motif Chemokines A...mentioning
confidence: 99%
“…Furthermore, the probability of obtaining an ICI benefit is significantly higher in the NLR low/TMB high group compared to the NLR high/TMB low group (OR = 3.22; 95% CI, 2.26–4.58; p < 0.001) [ 47 ]. CXCL13 in the tumor microenvironment of many different types of cancer, and CXCL13 is associated with favorable outcomes in cancer patients treated with ICIs [ 39 ].…”
Section: Other Potential Biomarkers For Icismentioning
confidence: 99%